Clinical Observation on Xituiyou Decoction Steam-wash Therapy for Knee Osteoarthritis with Wind-cold-dampness Arthralgia Syndrome - Dingyu ZHU; Guangwen WU; Guoping YE; Yinying LIN; Mingxia WU (康复学报)
Objective:To observe the clinical effect of Xituiyou decoction steam-wash therapy on knee osteoarthritis patients with wind-cold-dampness arthralgia syndrome, and explore the decoction effect on articular cavity hydrops.Methods:Atotal of 64 knee osteoarthritis patients with wind-cold-dampness arthralgia syndrome were randomly assigned to the treatment group and control group with 32 patients in each group. The treatment group received Xituiyou decoction steam-wash therapy 30 minutes each time, once a day, and the control group received external application with diclofenac diethylamine emulgel (Voltaren) three times a day, fifteen days as a course of treatment, and all patients lasted for a total of two courses of treatment. Symptom score, McGill pain score, and improvement of pathogenetic condition before and after treatment were used to evaluate the clinical effect of the decoction, and joint effusion content was detected.Results:Symptom score, pain score and joint effusion content of both groups were decreased after treatment compared with those before treatment (P<0.05), and the improvement of pathogenetic condition was better than that of before treatment (P<0.05).The decreasing amplitude of symptom score, pain score and joint effusion content in the treatment group after treatment were higher than those of the control group (P<0.05), the clinical effective rate and improvement of pathogenetic condition in treatment group were better than those of the control group (P<0.05).Conclusion:Xituiyou decoction steam-wash therapy has a positive effect on knee osteoarthritis patients with wind-cold-dampness arthralgia syndrome, and the decoction can promote the absorption of joint effusion.